Responses of Varroa-resistant honey bees (Apis mellifera L.) to Deformed wing virus - Khongphinitbunjong K. (2017)
© 2016 The negative impact of Deformed wing virus (DWV) on European honey bees Apis mellifera is magnified by Varroa destructor parasitism. This study compared the responses of two Varroa-resistant honey bee stocks, pure Russian honey bees (RHB) and out-crossed Varroa Sensitive Hygienic bees, Pol-line (POL) to DWV infection to that of Varroa- susceptible stock, Italian honey bees (IHB). Two-day-old larvae were fed with DWV lysate in different concentrations: undiluted DWV lysate (D1), D1:100, and D1:1000. The unfed larvae served as negative control. Combs containing test larvae were exposed to a common environment during their development using host colonies. Our results showed that only POL displayed variation in DWV levels when fed different DWV concentrations. POL fed highest concentration of DWV inoculum had the highest increase in DWV level than those fed low concentrations and unfed POL. This high increase in DWV level probably contributed to the decrease in the survival and median longevity (LT 50 ) of D1-fed POL. Weights of newly eclosed D1-fed POL were similar to those of the two controls and DWV-fed bees. However, within IHB, D1-fed bees showed significant reductions in weight, days of survival and LT 50 . Regardless of the concentrations of DWV inoculum, the DWV levels were similarly low within RHB; adult bees had similar weights. Overall, larvae fed D1 had the highest rate of wing deformation. POL and RHB had numerically lower proportions of bees with deformed wings. This study suggests that RHB showed some degree of resistant to DWV as shown by no reduction on weight and numerically lower proportion of wing deformity when compared with the other bee stocks.